Genetic pathways in nonalcoholic fatty liver disease: Insights from systems biology - Sookoian, Silvia Cristina (2020)
Nonalcoholic fatty liver disease (NAFLD) represents a burgeoning worldwide epidemic whose etiology reflects multiple interactions between environmental and genetic factors. Here we review the major pathways and dominant genetic modifiers known to be relevant players in human NAFLD and which may determine key components of the heritability of distinctive disease traits including steatosis and fibrosis. In addition, we have employed general assumptions which are based on known genetic factors in NAFLD to build a systems biology prediction model that includes functional enrichment. This new prediction model highlights additional complementary pathways that represent plausible intersecting signaling networks that we define here as a NAFLD-Reactome. We review the evidence connecting variants in each of the major known genetic modifiers (variants in PNPLA3, TM6SF2, MBOAT7, GCKR and HSD17B13) to NAFLD and expand the associated underlying mechanisms using functional enrichment predictions, based on both preclinical and cell based experimental findings. These major candidate gene variants function in distinct pathways, including substrate delivery for de-novo lipogenesis; mitochondrial energy utilization; lipid droplet assembly, lipolytic catabolism and fatty acid compartmentalization; and VLDL assembly and secretion. The NAFLD-Reactome model expands these pathways and allows for hypothesis testing as well as serving as a discovery platform for druggable targets across multiple pathways that promote NAFLD development and which influence several progressive outcomes. In conclusion, we summarize the strengths and weaknesses of studies implicating selected variants in the pathophysiology of NAFLD and highlight opportunities for future clinical research and pharmacologic intervention, as well as the implications for clinical practice.